Cost-Effectiveness Analysis (CEA) of Adjunctive Hyperbaric Oxygen Therapy to Standard Wound Care Alone in Diabetic Foot Ulcer (DFU) - Herdian Pradana; Afifah Machlaurin; Ayik Rosita Puspaningtyas; Fifteen Aprila Fajrin; Ainur Rokhmah (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Diabetic foot ulcer (DFU) is a chronic complication of diabetes mellitus that is associated with high treatment costs and an increased risk of amputation. Hyperbaric oxygen therapy (HBOT) has been used as an adjunctive therapy to improve wound healing, yet evidence regarding its cost-effectiveness in Indonesia remains limited. Aim: This study aimed to evaluate the cost-effectiveness of HBOT compared with standard care in patients with DFU. Methods: A retrospective observational analytic study was conducted involving 80 DFU patients treated at RS Paru Jember between January 2024 and September 2025, consisting of 37 patients receiving standard care with HBOT and 43 patients receiving standard care without HBOT. Result: Clinical outcomes assessed included wound status, pain status, duration of healing, and incidence of amputation. Cost analysis was performed from the hospital perspective using direct medical costs, and cost-effectiveness was evaluated using the Incremental Cost-Effectiveness Ratio (ICER). The results showed that the HBOT group had a significantly higher proportion of wound healing compared with the non-HBOT group (21.62% vs 4.63%) and a lower rate of wound deterioration (2.7% vs 20.93%) (p=0.001). Although the mean total treatment cost was lower in the HBOT group than in the non-HBOT group (IDR 11,737,388 vs IDR 14,177,692), the difference was not statistically significant (p=0.118). ICER analysis demonstrated negative values for all evaluated outcomes, including wound healing, pain improvement, healing within six months, and prevention of amputation, indicating cost savings. Conclusion: HBOT as an adjunctive therapy for DFU provides better clinical outcomes with lower overall treatment costs and may be considered a cost-effective and economically favorable intervention.